THE INFLUENCE OF POLIOXIPROPILENGLYCOLE WITH 500 MOLECULAR MASS ON OXIDATIVE PROCESSES AND NEUROTRANSMITTER METABOLISM UNDER LONG TOXIFICATION OF RATS - Vasylyeva, I.M.; Резуненко, Ю.К.; Zhernovaia, M.Ye.; Maksymova, I.G. (World of Medicine and Biology, 2015)
The inhibitory and excitatory neurotransmitters metabolism, state of oxidative processes under the long subtoxic L-502-2-10 action on rats in subacute experiment were studied. The choice of polyoxipropilenglycole with 500 molecular mass L-502-2-10, prevalently based on the the necessity to obtain a potential danger prognostic characteristics of xenobiotics for warm-blooded animals and pathochemical mechanisms of structural and metabolic disorders in the organism during prolonged subtoxic action in subacute experiment investigation. Effect of substance on oxidative processes and neurotransmitter metabolism was studied in subacute experiment on white laboratory rats weighing 190-200 g. Animals every day in the morning on empty stomach were administered the aqueous solution of L-502-2-10 rate of 1/10, 1/100 and 1/1000 DL50. Xenobiotics were administered orally via intragastric metal probe, per 60 days. After the animal toxification the content of biogenic amines and their precursors (serotonin, tryptophan, epinephrine, norepinephrine, dihydroxyphenilalanin, dopamine), inhibitory neurotransmitter - gamma-aminobutyric acid, glycine and taurine, and excitatory glutamate and aspartate were studied in their liver and brain. Subacute experiment revealed the increase of free radical processe levels in the liver and blood serum leukocytes. Research of catecholamine metabolism and their precursor DOPA showed a decrease of their content in the liver under the influence of 1/10 DL50 and increase - in the group of animals toxificated by 1/100 DL50. The investigation metabolism of biogenic monoamines and their precursors shows that xenobiotics in 1/100 DL50 activates adaptive and protective-adaptive mechanisms, accompanied by an increase ergo- and trophotropic functions, while the 1/10 DL50 it provides ergotropic exhaustion function. The results of biogenic monoamines and their precursors metabolism in the brain have shown that L-502-2-10 in 1/10 DL50 reduced content of DOPA, dopamine, norepinephrine, epinephrine and tryptophan against the background of increasing serotonin levels. The metabolically coupled neurotransmitter systems study showed: GABA - glutamate revealed increased content in the liver both glutamate and GABA under action of 1/10 and 1/100 DL50 «Laprol» Analysis of amino acid neurotransmitter metabolism indicates that the studied xenobiotics greater extent enhances glutamate content in the liver and in the brain - GABA. The inhibitory and excitatory amino acid content investigation in plasma of toxificated animals showed their decrease under the influence of xenobiotics in both 1/10 and in 1/100 DL50. The decrease in plasma inhibitory and excitatory amino acids, possibly due to the mobilization of recovery synthesis, which giving substrates aimed at maintaining homeostatic functions under high stress adaptation mechanisms. Results of the study show that L-502-2-10 polyoxipropilenglycole in 1/100 and 1/10 DL50 in conditions of long subtoxic effect on rats, able to lead to accumulation in the liver and leukocytes •O2- by increasing the activity of microsomal and mitochondrial electron-transport chains, which are generators of reactive oxygen species. Xenobiotics in 1/10 and 1/100 DL50 violated biogenic amine and their precursor metabolism in the liver and brain. L-502-2-10 in 1/100 DL50 leads to ergotropic and trophotropic function activation both in the liver and in the brain. In 1/10 DL50 "Laprol" provides a the failure of adaptive and protective-adaptive mechanisms to support the homeostatic body functions.